Reactivity of 4‐Vinyl‐2H‐1‐benzopyran‐2‐ones in Diels–Alder Cycloaddition Reactions: Access to Coumarin‐Based Polycycles with Cdc25 Phosphatase‐Inhibiting Activity. Issue 14 (27th March 2013) - Valente, Sergio; Xu, Zhanjie; Bana, Emilie; Zwergel, Clemens; Mai, Antonello; Jacob, Claus; Meiser, Peter; Bagrel, Denyse; Silva, Artur M. S.; Kirsch, Gilbert
Abstract: The reactivity of 4‐(1‐butoxyvinyl)‐2 H ‐chromen‐2‐one (1 ) and ( E )‐4‐(2‐butoxyvinyl)‐2 H ‐chromen‐2‐one (2 ) as diene in thermal Diels–Alder cycloaddition reactions with several electron‐poor dienophiles is reported. Among several dienophiles used in this study 1, 4‐benzoquinone afforded cycloadducts 11‐butoxy‐1 H ‐naphtho[1, 2‐ c ]chromene‐1, 4, 5‐trione (3e ) and 1 H ‐naphtho[1, 2‐ c ]chromene‐1, 4, 5‐trione (4g ) that showed Cdc25 phosphatase‐inhibition activity at low micromolar values, with both compounds more effective against Cdc25 A and Cdc25 C isoforms. Abstract : The reactivity of 4‐(1‐butoxyvinyl)‐2 H ‐chromen‐2‐one (1 ) and ( E )‐4‐(2‐butoxyvinyl)‐2 H ‐chromen‐2‐one (2 ) in thermal Diels–Alder cycloaddition reactions is reported. Among the cycloadducts obtained compounds3e and4g inhibited Cdc25 phosphatase activity at low micromolar values.